Institutional Diversity in Ontario’s University Sector: A Policy Debate Analysis - Piche, Pierre Gilles; Jones, Glen (Canadian Journal of Higher Education, 2016)
In order to meet the demands in a cost-effective manner of an emerging knowledge society that is global in scope, structural higher education policy changes have been introduced in many countries with a focus on systemic and programmatic diversity. There has been an ongoing debate about institutional diversity in Ontario higher education, especially within the university sector, for at least five decades. This paper will provide insight into issues of quality, accessibility, and funding through the lens of the current policy debate about institutional diversity by using document and policy analysis, and by drawing on a number of semi-structured interviews with senior university and system-level administrators.